ISOLASI DAN KARAKTERISASI BAKTERI PENDEGRADASI FENOL DARI LIMBAH CAIR RUMAH SAKIT UMUM DAERAH (RSUD) ARIFIN ACHMAD PEKANBARU - Rahmy Juwita; Bernadeta L. Fibriarti; Rodesia M. Roza (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Phenol is a toxic organic compound found in hospital liquid waste. This research was conducted to obtain bacterial isolates that can be used for degrading agent in the microbiologically liquid waste control without harmful side product. Samples weretaken from the liquid waste tank, at Arifin Achmad Hospital Pekanbaru, then the phenol countent was counted using a folin-ciocalteau method. The isolation of phenol degrading bacteria used enrichment culture method in microbiology laboratory of Faculty of Mathemathic and Science, Riau University. The next steps were to purify isolates purification, to test the ability of phenol degradation and also to obtainmorphological characteristic (simple and gram staining) and to have some biochemical tests (MR-VP test, catalase test, carbohydrates fermentation, simmon’s citrate test, casein hydrolysis and indole test). The results showed that phenol content in the samples ranged from 2 to 6 ppm, then 6 bacterial isolates were randomly selected and grown at ramsay medium and enriched with phenol in 48 hour incubation time. The shapes of selected isolates were bacilli and gram negative. The highest degradation rate was on MJEQ1 isolates (10 ppm/hour) and the lowest degradation was on MJST2isolates (7,2 ppm/hour).